Program Pelatihan Analisis Data Kuantitatif Dalam Bidang Manajemen Keuangan Untuk Meningkatkan Mutu Penulisan Karya Ilmiah Di STIE Latifah Mubarokiyah - Fitriani; Setiana, Adi Robith; Dewi, Lati Sari; Ramdan, Rhaka Saepul; Latifah, Risma Nurul (CV. SINAR HOWUHOWU, 2025)
Quantitative data analysis skills are essential for financial management students in producing high-quality, data-driven scientific writing. However, many students still face difficulties in understanding statistical methods and applying them appropriately in research. This training program aims to enhance students’ conceptual understanding and practical skills in quantitative data analysis to improve the quality of scientific writing at STIE Latifah Mubarokiyah. The program was implemented through interactive lectures, hands-on practice using statistical software, and discussion sessions, supported by pre-test and post-test evaluations. The results indicate a significant improvement in participants’ understanding of quantitative data analysis concepts, their ability to process and interpret financial data, and the overall quality of scientific writing, particularly in the research methodology and discussion sections. The training program proved effective in strengthening students’ research competencies and contributed positively to fostering a data-driven research culture at STIE Latifah Mubarokiyah. Therefore, similar programs are recommended to be conducted continuously and further developed with advanced analytical materials.